Torsion Testis: Surgical Management - Uddin, Md Nasir; Abedin, Kazi Rafiqul; Razzaque, Kazi Zakirul; Hoque, Md Serajul; Hasan, Md masum; Shamim, Md monowarul Haque (Bangladesh Journal of Urology, 2020)
Objective: Acute testicular torsion is a urological emergency that require quick accurate diagnosis and timely surgical intervention to salvage the testis. Nature of surgical management depending on viable or non viable testis during surgical exploration. Materials and methods: This retrospective study was conducted at some private hospital in Dhaka city and Comilla from June 2006 to February 2011. The study enrolled 36 patients with age range 7 to 23 years, mean age was 14 years. Twenty one (58.33%) patients reached hospitals within 4 to 6 hours from onset of pain, 7(19.44%) patients within 12 hours, 3(8.33%) patients within 24 hours, 2(5.55%) patients within 2 days and 3(8.33%) patients after 5 days of onset pain. All patients underwent surgical exploration. Results: Twenty four (66.66%) patients showed viable testis on exploration and orchidopexy were done on ipsilateral testis with prophylactic orchidopexy on contralateral site. Another 12 (33.33%) patients had nonviable testis, required orchidectomy on involved testis and prophylactic orchidopexy on opposite testis. Conclusion: Spermatic cord torsion represents a commonly encountered urological emergency where accurate diagnosis and timely intervention are essential for functional and nonatrophied testicular salvage. Bangladesh Journal of Urology, Vol. 15, No. 1, Jan 2012 p.3-5